Study on Stability Control of Gob-Side Entry Retaining Structure Without Filling Wall in Hard Roof - Jing-kui, Long; Chao-xin, Qi; Zuo-yong, Cao; Hong, Lan; Wen-kai, Yu (Frontiers in Earth Science, 2022)
In view of the deformation and instability law of hard roof without filling wall gob-side entry retaining, based on the systematic construction and analysis of the force and bearing model of gob-side entry retaining structure, the control mechanical model and calculation method of gob-side entry retaining are put forward, in which the anchor roof beam and the key block above form cantilever beam together, and the anchor solid coal side is the foundation support. The research and practice show that: under the condition of hard roof, the mechanical connection between the roof of gob-side entry retaining and the roof of mining face can be effectively cut off, so as to improve the structural configuration and mechanical properties of the lateral roof of gob-side entry retaining and the key blocks above, and reduce the damage of upper strata subsidence and goaf roof collapse to the roof of roadway. Then, through the implementation of collaborative and strengthen anchorage, significantly enhanced the anchoring solid coal help, bearing capacity of anchor roof beam, jointly undertake deflection load generated by the upper strata and mining influence, coupled with the roof bolting, reinforcement of waste rock bolting supporting role, can improve the structure for better stability, adaptability and engineering applicability, and successfully applied in engineering practice, It is worthy of further research and application.